Peptide Bond Formation Between the Hetrosubunits of ω-Transaminase, Alanine Dehydrogenase, and Formate Dehydrogenase Through Subunit Splicing Promoted by Heterodimerization of Leucine Zipper Motifs - Li, Rong; Chen, Yao; Du, Kun; Feng, Wei (Frontiers in Bioengineering and Biotechnology, 2020)
For the multimeric enzymes R-ω-transaminase (RTA), alanine dehydrogenase (AlaDH), and formate dehydrogenase (FDH), peptide bond formation between the hetrosubunits has been achieved by the intein-mediated in vivo subunit splicing. The subunit ligation is triggered by the heterodimerization of an arginine rich leucine zipper motif with a glutamic acid rich leucine zipper motif. The one-by-one ligation of hetrosubunits constructs the pairing enzymes RTA&AlaDH and AlaDH&FDH. The ligation modes were analyzed based on blue native polyacrylamide gel electrophoresis (BN-PAGE). The spectra of circular dichroism (CD), fluorescence, and two-dimensional FTIR provide information on the secondary structures and stability of the pairing enzymes. The enzyme-substrate interaction was analyzed based on microscale thermophoresis analysis. In contrast to the mixed three enzymes RTA + AlaDH + FDH, the ligated enzymes RTA&AlaDH + AlaDH&FDH exhibited a much larger substrate affinity, higher stability, and significantly enhanced activity.